The effect of the elliptical front wall on energy conversion performance of the offshore OWC chamber: A numerical study. (15th September 2022) - Qu, Ming; Yu, Dingyong; Xu, Zhigang; Gao, Zhiyang
Abstract: The configuration of the front wall has an obvious influence on the effect energy conversion effect of the offshore OWC devices. In order to improve the energy conversion effect of the OWC device, a new elliptic front wall structure for the offshore OWC chamber was proposed in this paper. The variation of pressure, outlet air flow and free surface height of the chamber were studied by numerical simulation, with the change in the angle of elliptical front wall ( β  = 0, 5, 10, 15, 20, 25, 30), and under the wave condition of relative wavelength L / B  = 4.0–9.0. Based on the results, the effect of the elliptical front wall angle on the energy conversion efficiency of the offshore OWC chamber were analyzed. The main results are as follows: Compared with the rectangular front wall, the elliptical front wall can effectively improve the energy conversion effect. The elliptical front wall with β  = 25 has the best comprehensive effect under the test wave condition. With the influence of it, the wave energy conversion efficiency ξ is about 25% higher than the chamber with the common rectangular front wall( β  = 0). The results can be used as a reference for the design of OWC devices. Highlights: Elliptical front wall structure can improve the wave energy conversion performance. Elliptical front wall structure can avoid the vortex in front of the chamber. Elliptical structure with smaller eccentricity is better when wavelength is bigger. Elliptical front wall structure of 25°get better effect on the conversion efficiency.